Other functions of the reinforcer: reflections on the description of reinforcement (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Usually, novice behavior analysts are thought that the reinforcement is exclusively defined by the increase in frequency or rate of a single response class. Based on the datum available on literature, we discuss the pertinency of the standard theory of reinforcement, and we pursue a broader description of the following functions: (1) selection; (2) induction; (3) ordination and organization; and (4) expansion of behavioral repertoire. Even though the convenience of taking frequency as a unit of measurement, the standard theory of reinforcement lacks of comprehensiveness when fails to describe its relations with phylogeny, with another response classes besides the one that reinforcer is made contingent to, and with the indirect outcomes of the systematic application or reinforcement. A theory restricted to the measure of frequency or rate is no longer tenable, considering the datum available on operant literature.
Keywords: Reinforcement; Functions-of-reinforcer; Induction; Ordination-organization; Behavioral-repertoire